Legal ethics for tracing the roots of corruption in Indonesia - Hehanussa, Deassy JA; Pede, Albert (Journal of Law Science, 2024)
The purpose of this study is to investigate how the principles of legal ethics may be used to find and eliminate the sources of corruption in Indonesia. Legal ethics provides a framework for evaluating legal acts and regulations in light of their ethical implications by incorporating moral principles within the legal profession. Legal statutes, administrative rules, judicial rulings, and scholarly articles are the main and secondary sources consulted in this normative qualitative study. To conduct a normative analysis, one must first determine the efficacy of the current legal framework in eliminating corrupt activities, and then assess the application of legal ethical standards within that framework. According to the findings, flaws in the legal system that permit corruption may be identified by using ethical principles of law, such as fairness, honesty, accountability, and respect for human rights. Justice requires that the law be applied without bias or prejudice, and integrity guarantees that everyone participating in the judicial system is forthright and honest. The public's faith in the justice system depends on its honest administration, and the public may rest certain that its representatives will always put the public interest first because of their moral and professional obligations. Human rights compliance guarantees that anti-corruption initiatives safeguard victims' rights while also punishing those responsible for wrongdoing